The Variant of Learning Method in Speaking Skills Through Personal Experiences: Narrative Inquiry - Pedja Rifki Azizi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: A lot of aspects of social growth in the last few years. Significantly education changes a lot in teaching strategies, learning methods, and learning sources. Back then, people used books to find knowledge and information, but seeing from a contemporary perspective, getting news and information has become much easier and faster with the help of technology. They referred to the researcher who experienced both the traditional and modern eras. The researcher, who experienced both traditional and contemporary ways, decided to use his learning experiences as a topic study. This study analyses the researcher's experiences learning English from junior to undergraduate. Using autobiography as a data source becomes much easier for the researcher to find significant moments and analyze the researcher's stories using Webster and Matorva's in-depth analysis styles. Also, the study based on descriptive qualitative with a narrative approach makes a lot of descriptions and explanations about the researcher's stories using a variant of the method. The result of this study becomes four sub-point. The first point of interest researcher finds interest in English from social media. The second point is hobbies; from doing hobbies intentionally, the researcher gain vocabulary doing those hobbies. The third point is motivation; the researcher found the motivation to learn more English in the future after he got a compliment from his teacher in senior high school. The last point is self-reflection; the researcher observes or reflects on his activities to find a weakness in his abilities and a suitable strategy for his learning progress. The analysis shows important moments in researcher learning progress from junior to university contribute a lot to constructing researcher speaking skills using the variant learning method. Second, the researcher used a variant learning method to improve his speaking skills, like using repeated reading to increase vocabulary and combining two strategies with the support of online friends to help the researcher improve his speaking abilities, including other skills. Last, readers get motivation and information about managing learning strategies more carefully after reading researcher stories.Keywords:Â Learning process, experiences, speaking